MUROTTAL AL-QURAN THERAPY TO INCREASE SLEEP QUALITY IN NURSING STUDENTS - Enggal H Kurniyawan (UNEJ e-Proceeding)
Background: Learning schedules are densely packed, tasks and homework make students stress and fatigue so that interfere with their quality of sleep. This study aims to analyze murottal Alquran in improving sleep quality. Methods: This research method used quasi experimental design with the Pre-test-Post-test approach. The sampling technique used accidental sampling with control and treatment group. The number of samples used is 30 students. Sleep quality is measured using the Pittsburgh Sleep Quality Index. Results: There was a significant difference sleep quality (p = 0.001) in the treatment group and no significant difference in the control group (p = 1,000). There was a significant difference in murrotal alquran therapy in improving sleep quality (p = 0.001) between treatment group and control group. Conclusions: Murrotal al-Quran therapy effective to improve sleep quality in nursing students of Jember University Keywords: murottal, alquran, sleep, quality